Phonetic Tonal Manifestations and Trends in Tone Change: A Case Study of the Yong-Deng Dialect in Northwest China - Li Yi (Languages, 2023)
This study takes the Yong-deng dialect as a case study to investigate the phenomenon of tonal merging observed in Northwest Chinese dialects. It begins by examining the various monosyllabic tone patterns of the Yong-deng dialect, then supplements this with a review of the relevant literature, comparisons with the tone patterns of the neighbouring dialects, and an analysis of its tone sandhi in disyllabic and trisyllabic combinations. Each step of the dialect’s tonal variation is scrutinised, allowing for the identification of pertinent phonetic biases and the derivation of associated phonological rules. The central argument advanced here is that both synchronic tonal variation and diachronic tone change are governed by specific phonological rules. Despite the ostensibly variable phonetic manifestations, these rules can enable the prediction of the trajectory of tone change. The paper contributes to the understanding of tone merger and highlights its systemic and rule-bound nature.